Chinese pension system : Opportunities for the improvement (2023) - Zhang, Yifan; Brabec, Petr; Štěpánek, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2023)
By analyzing provincial panel data from 2012 to 2021, this thesis explores the factors affecting basic pension expenditure in China by making full use of economic principles and relevant public policies and makes recommendations for improvements that can be made in the future. The main objective is to identify the effects of mortality rates and pension replacement rates on the total level of pension expenditures, so as to assess the feasibility of delaying retirement policies and adjusting pension benefit mechanisms to alleviate the pension expenditure problem. The research methodology includes a review of existing studies on China's pension system, international comparisons with countries such as the United States, Japan, and some European countries, and rigorous panel data regressions using STATA software. The results of the study indicate that an increase in mortality decreases pension expenditures, suggesting the urgency of delaying retirement policies as an increase in medical care and the consequent increase in life expectancy increases pension expenditures. In addition, the pension replacement rate mechanism is positively related to spending, suggesting that adjusting pension benefits and related mechanisms can address the spending problem. The study also reveals regional differences in the development of China's pension system, particularly urbanization in the central, eastern, and western regions. Notably, China's pension system is not indexed to inflation, which could lead to potential problems with low replacement rate of older pensioners in the future.
Vedoucí práce: Petr Brabec
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: economics and public policy [obor dipl. práce]; diplomové práce; master's theses